The Influence Of Demographic Factors And Financial Literacy On Investment Decisions Mediated By Behavioral Finance (Empirical Study: On Capital Market Investors In DKI Jakarta) - Hansen Andersson (Journal Research of Social Science, Economics, and Management, 2023)
Financial literacy is only one of many aspects that have a role in the choice of investments to make. This study investigates how knowledge of behavioral finance might influence investing choices for those with a basic understanding of personal finance. In this study, we used a structural equation modeling (SEM) approach. This finding demonstrates that financial knowledge has a role in moderating undesirable actions. Similarly, investment choices benefit from both financial knowledge and behavioral finance as a mediator. Market momentum may be gained if individual investors engage in behavior that can be managed via careful preparation and the use of sound financial principles. Which aids in maximizing profit, improving investment and portfolio performance, minimizing risk, making more informed investment decisions, and coming up with effective trading methods.